1992
DOI: 10.1002/ffj.2730070605
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of elemental sulphur in capers (Capparis spinosa L.) and first investigation of the flavour profile

Abstract: As a result of a positive response to a dithiocarbamate test, the sulphur content of caper volatiles has been investigated by GC‐MS. In addition to sulphides, isothiocyanates and other flavour molecules, elemental sulphur (S8) was identified for the first time in a non‐processed food. This paper presents the primary description of the aromatic bud which is widely consumed in Mediterranean countries. The organoleptic profiles of uncommon thiocyanates, nitriles and of the elemental sulphur are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 9 publications
1
35
0
3
Order By: Relevance
“…iy=/cS/(Ks+S) (3) lo que se confirma por la linealidad de la representación 1/L/vs MS (representación de Lineweaver-Burk, figura 2) para las cuatro concentraciones de sustrato utilizadas como alimento: 1/Í;=1//C+(/<S//C)(1/S) (4) donde k (g DQO/g SSV día) es la velocidad máxima de utilización de sustrato y Ks (g DQO/I) es la constante cinética del proceso.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…iy=/cS/(Ks+S) (3) lo que se confirma por la linealidad de la representación 1/L/vs MS (representación de Lineweaver-Burk, figura 2) para las cuatro concentraciones de sustrato utilizadas como alimento: 1/Í;=1//C+(/<S//C)(1/S) (4) donde k (g DQO/g SSV día) es la velocidad máxima de utilización de sustrato y Ks (g DQO/I) es la constante cinética del proceso.…”
Section: Resultados Y Discusiónunclassified
“…Fermented products are greatly appreciated for their flavour, appetite and digestive properties (1,2). Pungent flavour is due to several sulphur containing compounds made by the fermentation of glucosids (3). If finished product is used in conjunction with other foods, it supports flavour or is used as garniture (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the analgesic, anti-inflammatory, antihepatotoxicity, hypolipidemic, and anti-allergic effects of this plant have been reported (5)(6)(7)(8)(9). Research on C. spinosa reveals the presence of such compounds as alkaloid, lipids, polyphenols, flavonoids, and glucosinolates (10). It also has certain flavonoids, such as kaempferol, rutin, and quercetin (11)(12)(13), and thus this plant used as a remedial source.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, this plant is used as a diuretic and as way a treatment for gout, rheumatism and liver disease. Different studies have reported the analgesic, anti-hepatotoxic, anti-allergic, and hypoglycemic, hypolipidemic and anti-allergic effects (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%